The Effect of Cirata Reservoir Sediment on Early Developmental Stage of Common Carp (Cyprinus carpio) Embryo - Yuni Pujihastuti; K. Nirmala; I. Effendi (Jurnal Akuakultur Indonesia)
Sedimentation at Cirata reservoir may directly and indirectly influence fish particularly fish which have an adhesive characteristic at its early developmental stage such as common carp (Cyprinus carpio). Sample of sediment was collected from Cirata reservoir using Eikmand dredge at a depth of 80 m. The sample was subsequently centrifuged at 5500 rpm for 10 min. The supernatant obtained was then used for toxicity test on common carp at early developmental stage. In this test, four treatments were applied based on the concentration of sediment supernatant, namely: 0, 8.33, 16.60 and 24.90 %. The results showed that a higher sediment supernatant concentration resulted in lower egg yolk absorption rate, lower relative growth rate in length, lower egg yolk efficiency and higher egg and larval abnormality.  Higher sediment supernatant concentration also resulted in lower hatching percentage of common carp larva. The damage of eggs and larval morphologies in treatments with sediment supernatant was likely caused by the presence Pb and organic matters which act in synergy.